Relations Between Intimate Partner Violence and Forgiveness Among College Women. (November 2015) - Davidson, M. Meghan; Lozano, Nicole M.; Cole, Brian P.; Gervais, Sarah J.
The purpose of the current investigation was to examine forgiveness and intimate partner violence (IPV) among college women. Undergraduate women ( N = 502) participated in an online study in which overall experiences of IPV, as well as experiences of psychological and physical IPV, were investigated with respect to transgression-specific and dispositional forgiveness. Simultaneous multivariate regressions revealed that (a) the experience of IPV was associated with higher levels of avoidance and revenge, and lower levels of benevolence, forgiveness of self, forgiveness of others, and forgiveness of uncontrollable situations; (b) types of IPV demonstrated differing impacts on forgiveness; and (c) the mere experience of IPV is more salient than its frequency.